Effectiveness of the Med Safety mobile application in improving adverse drug reaction reporting by healthcare professionals in Uganda: a protocol for a pragmatic cluster-randomised controlled trial. Issue 7 (1st July 2022) - Kiguba, Ronald; Mwebaza, Norah; Ssenyonga, Ronald; Ndagije, Helen Byomire; Nambasa, Victoria; Katureebe, Cordelia; Katumba, Kenneth; Tregunno, Phil; Harrison, Kendal; Karamagi, Charles; Scott, Kathryn A; Pirmohamed, Munir
Abstract : Introduction: Combination antiretroviral therapy (cART) has massively reduced HIV mortality. However, long-term cART increases the risk of adverse drug reactions (ADRs), which can lead to higher morbidity, mortality and healthcare costs for people living with HIV (PLHIV). Pharmacovigilance—monitoring the effects of medicines—is essential for understanding real-world drug safety. In Uganda, pharmacovigilance systems have only recently been developed, and rates of ADR reporting for cART are very low. Thus, the safety profile of medicines currently used to treat HIV and tuberculosis in our population is poorly understood. The Med Safety mobile application has been developed through the European Union's Innovative Medicines Initiative WEB-Recognising Adverse Drug Reactions project to promote digital pharmacovigilance. This mobile application has been approved for ADR-reporting by Uganda's National Drug Authority. However, the barriers and facilitators to Med Safety uptake, and its effectiveness in improving pharmacovigilance, are as yet unknown. Methods and analysis: A pragmatic cluster-randomised controlled trial will be implemented over 30 months at 191 intervention and 191 comparison cART sites to evaluate Med Safety. Using a randomisation sequence generated by the sealed envelope software, we shall randomly assign the 382 prescreened cART sites to the intervention and comparison arms. Each cART site is a cluster that consists of healthcare professionals and PLHIV receiving dolutegravir-based cART and/or isoniazid preventive therapy. Healthcare professionals enrolled in the intervention arm will be trained in the use of mobile-based, paper-based and web-based reporting, while those in the comparison arm will be trained in paper-based and web-based reporting only. Ethics and dissemination: Ethical approval was given by the School of Biomedical Sciences Research and Ethics Committee at Makerere University (SBS-REC-720), and administrative clearance was obtained from Uganda National Council for Science and Technology (HS1366ES). Study results will be shared with healthcare professionals, policymakers, the public and academia. Trial registration number: PACTR202009822379650.